Association between levels of synovial anti-citrullinated peptide antibodies and neutrophil response in patients with rheumatoid arthritis - Gorlino, Carolina Virginia (2018)
Rheumatoid arthritis (RA) is characterized by the presence of anti-citrullinated peptide antibodies (ACPAs) and neutrophils infiltrating the synovial fluid (SF) of the affected joints. The aim of this work was to analyze whether the presence of ACPAs in SF is associated with neutrophil infiltration and with their phenotype in the inflamed joints of RA patients. We found that in the presence of ACPAs, the number of synovial neutrophils correlated with severe disease activity. The SF were divided according to synovial ACPA levels in negative- (<25 U/mL), low- (25–200 U/mL) and high level (˃200 U/mL; ACPA high ). We observed that IL-6, IL-17, and IL-8 were significantly elevated in ACPA high SF and that IL-8 levels correlated positively with neutrophil counts and with worse clinical manifestations. Additionally, in vitro incubation of neutrophils with ACPA high SF resulted in an increased ROS production and extracellular DNA release compared to neutrophils incubated with ACPA-negative SF. These exacerbated effector functions were associated with a fraction of ICAM-1-positive neutrophils, which were induced by ACPA high SF. Likewise, in in vivo, we could also detect this subset among neutrophils present in ACPA high SF. In conclusion, the data presented here shed light on the role of SF-ACPAs as inductors of a proinflammatory profile in neutrophils.